Implementation Of Resolution Of Juvenile Criminal Cases From The Criminal Justice Process To A Process Outside Of The Criminal Justice System (Diversion) - Adewiyah, Rhabiatul; Hilman, Didi; Lestari, Nisa (Universitas Ibn Khaldun Bogor, 2023)
Children are regarded as valuable assets to society and the nation, requiring appropriate attention and care in order for them to undergo growth and development into healthy, happy, and successful individuals in the future. The increasing rate of juvenile delinquency year after year has various causes. Factors that contribute to juvenile delinquency leading to a child's involvement in criminal cases, and ultimately legal proceedings, include a lack of parental attention, pressure to meet livelihood demands, and feelings of desperation. In order to ensure protection for children involved in criminal acts, a diversion approach is adopted as an effort to resolve juvenile criminal cases without involving the juvenile justice process. Diversion provides an opportunity for children to rectify their mistakes and restore positive relationships, in line with Article 7 of Law Number 11 of 2012 on the Juvenile Criminal Justice System. The diversion process can be applied during the stages of investigation, prosecution, and court examination. The Law on the Juvenile Criminal Justice System regulates diversion in Articles 8 and 9, listing the conditions that must be met. One crucial requirement is that diversion must be done in the best interest of the child, following restorative justice principles, and involving the juvenile offender, juvenile victim, parents, social workers, and community guidance personnel. Furthermore, diversion is also subject to the condition that the offender has a criminal record of less than seven years and does not have a history of repeated criminal acts.